Aging Effect on Microstructure and Machinability of Corrax Steel - Guldibi, A. S.; Demir, H. (Engineering, Technology & Applied Science Research, 2020)
In this paper, the influence of the aging process on the microstructure and machinability of Corrax Steel was investigated for four samples: a solution heat-treated (A0) and three samples aged at 400ºC (A4), 525ºC (A5.25) and 600ºC (A6) for four hours. The effect of aging temperature on hardness was examined. Machining tests were carried out using a CNC lathe with a multi-layer coated PVD (AlTiN) cutting tool, at various cutting speeds (50, 100, 150, 200, 250, 300, 350m/min) with constant feed rate (0.1mm/rev) and 1mm constant cutting depth. The microstructure was investigated using an optical microscope and EDS attached SEM. The effect of aging on reverted austenite formation was also evaluated. In order to understand the changes in surface topology, cutting forces and vibrations were measured. With increasing aging temperature, the lath martensite was transformed to plate martensite because of the formation of precipitates and reverted austenite. Aging at different temperatures increased hardness up to 58%, cutting forces up to 117% and surface roughness up to 450%. The results describe the effect of the aging treatment on cutting forces, surface topology, tool wear and vibrations.